Novel Betaherpesvirus in Bats - Watanabe, Shumpei; Maeda, Ken; Suzuki, Kazuo; Ueda, Naoya; Iha, Koichiro; Taniguchi, Satoshi; Shimoda, Hiroshi; Kato, Kentaro; Yoshikawa, Yasuhiro; Morikawa, Shigeru; Kurane, Ichiro; Akashi, Hiroomi; et al. (Emerging infectious diseases, 2010)
Because bats are associated with emerging zoonoses, identification and characterization of novel viruses from bats is needed. Using a modified rapid determination system for viral RNA/DNA sequences, we identified a novel bat betaherpesvirus 2 not detected by herpesvirus consensus PCR. This modified system is useful for detecting unknown viruses.